Heracleum sosnowskyi seed development under the effect of exogenous application of GA3 - Dalia Koryznienė; Sigita Jurkonienė; Tautvydas Žalnierius; Virgilija Gavelienė; Elžbieta Jankovska-Bortkevič; Nijolė Bareikienė; Vincas Būda (PeerJ, 2019)
Numerous studies have demonstrated the impact of exogenous gibberellin on fleshy fruit formation, but the effect on dry fruits is not yet well known. To test the role of gibberellin (GA3) in dry fruit formation, we analysed the impact of exogenous GA3 on the invasive plant Sosnowsky’s hogweed (H. sosnowskyi Manden.) seed development and germination. Treatment of GA3 concentrations of 0.07 mM, 0.14 mM, 0.28 mM, 0.43 mM was applied to flowers at the early stage of development. Seeds were collected from treated satellite umbels. It was observed that GA3treatment did not have a significant effect on the size of H. sosnowskyi seeds, but caused various changes in their shape. The data on semi-thin longitudinal sections of H. sosnowskyi mericarps and SEM micrographs of embryos showed that the embryos in GA3 (0.43 mM) treated variants were at torpedo stage, while in control variants—mature embryos. The germination of seeds of each variant was estimated by burying them in the soil. Our studies indicated that GA3 application reduced the germination of H. sosnowskyi seed from 98.0% (control) to 16.5% (GA3 concentration 0.43 mM). It was assumed that exogenous application of GA3 had influence on the development of dry Sosnowsky’s hogweed seeds and could be used to inhibit the spread of this invasive plant.